Eosinophilic Gastroenteritis in the Setting of Colorectal Neoplasia - Yi Sien Koo; June Oo; Suat Chin Ng (World Journal of Colorectal Surgery)
Eosinophilic gastroenteritis is a rare inflammatory disease of one or more segments of the gastrointestinal tract. Clinical features vary depending on the site and layer of involvement. We present a case of a 61-year-old female with malignant colonic obstruction and several months of abdominal discomfort, nausea, and altered bowel habits. She had a colonic stent as a bridge to her definitive surgery. She continued to have diarrhea and abdominal discomfort until her definitive surgery. Interestingly, histopathology showed colonic cancer with segments of eosinophilic colitis. This is a unique case given the rarity of eosinophilic gastroenteritis and its potential predisposition to neoplastic disease. We review the clinical and pathological features of eosinophilic gastroenteritis and the possible linkage with colorectal cancer.